Using UV-Vis. linear dichroism to study the orientation of molecular probes and biomolecules in lipidic membranes. Issue 2 (2003) - Castanho Castanho, M. A. R. B. M. A. R. B.; Lopes Lopes, S. S.; Fernandes Fernandes, M. M.
Abstract : Linear dichroism methodologies are based on the different interaction of molecules with linearly polarized light depending on their orientation. Theoretical predictions are used to conclude on the orientation of selected molecules relative to their neighbours (usually an organized matrix). In the specific case of linear dichroism methodologies applied to data obtained from UV‒Vis. spectroscopic techniques, the orientational distribution function of the chromophores' electronic transition moment can be calculated and converted to the molecular axis distribution function. In this paper, the orientation of molecular probes and biomolecules in model systems of biomembranes (lipidic matrixes) is explored and illustrated using common membrane probes ( trans ‒parinaric acid, a cyanine and laurdan) and polyene antibiotics (Amphotericin B and Nystatin). The emphasis is on the technique and methodologies themselves, rather than the scientific impact of the attained distributions. The main addressed items are: (1) How to adapt a common UV‒Vis. spectrophotometer and spectrofluorimeter to perform linear dicrhoism experiments?, (2) Sample preparation, and (3) Data analysis (including artefacts corrections).